Rendimento quântico e trocas gasosas em maracujazeiro amarelo sob salinidade hídrica, biofertilização e cobertura morta - Freire, José Lucínio De Oliveira (2014)
The experiment was conducted in Remigio, Paraiba State, to evaluate the responses of yellow passion fruit (Passiflora edulis Sims f. flavicarpa Degener) related to photosynthetic efficiency and gás exchange, mineral nutrition, water consumption yield and water use efficiency by plants. The experimental design was randomized blocks in a 2 x 2 x 2 factorial, related to irrigation with not saline (0.5 dS m-1) and saline water (4.5 dS m-1), soil with and without biofertilizer, with and without mulch, in three replications. Three plants were maintained in plastic containers used as pressure circular lysimeters with 130 dm³ volume and drains to the leaching of salts excess. Irrigation water with low salinity and application of biofertilizer common stimulated photosynthetic efficiency of plants. Simultaneous use of high salinity water, fertilizer and mulch to reduced stomatal conductance of yellow passion fruit. Plants under salt stress have photochemical activity of photosystem II and inhibited net photosynthesis.